PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI PROVINSI SULAWESI UTARA - Clinton Fernando Wilar; Sherly G. Jocom; Caroline B. D. Pakasi (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The objective of this research is to find out the Role of the Agricultural Sector in North Sulawesi whether the Agriculture sector becomes a base or non-base sector in the present and in the future. Data used in this research in secondary data, namely North Sulawesi GRDP (2010 ADHK) and Indonesia's GDP (ADHK 2010). Analysis used in this research is the analysis of Location Quotient (LQ), Analysis of Dynamic Location Quotient (DLQ), Comparison of LQ and DLQ.Based on the results of the research by using LQ (Location Quetient) analysis, the agricultural sector is a base sector in the economy in North Sulawesi Province. Almost all agricultural sub-sectors are the base sector, except for the Forestry and Logging sub-sector. Based on the results of the DLQ (Dynamic Location Quetient) analysis, there is a change in the economic base. Which is predicted to be the base sector in the future, namely Horticulture and Animal Husbandry.Keywords: Role of Agricultural sector – North Sulawesi Economy